Analysis of Legal Protection for the Debtors Against Abuse of Circumstances Committed by Creditors in Forming a Sale and Purchase Agreement - Araningrum Widiati Hutami; Rachmi Sulistyarini; Mohammad Hamidi Masykur (Universitas Negeri Semarang, 2023)
In a debt contract for a large nominal amount, there is a guarantee objects for which the debtor is responsible for the loan received from the creditor, one of the objects is land rights. Creditor often take a shortcut to execute collateral assets through the use of land rights sale and purchase contract procedures when debtor is unable to pay their debts, the establishment of the sale-purchase agreement was made with unbalanced circumstances between the parties. In Indonesia there are no legal regulations about the abuse of circumstances as a form of defect in the will of an agreement, therefore the debtor in forming a land rights sale and purchase agreement also does not get legal protection from legal regulations.